2022
DOI: 10.2174/1871525719666210809122541
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects and in-silico Antioxidant Mechanism of L-Ergothioneine in Experimental Type-2 Diabetic Rats

Abstract: Background: Diabetic cardiotoxicity is commonly associated with oxidative injury, inflammation, and endothelial dysfunction. L-ergothioneine (L-egt), a diet-derived amino acid, has been reported to decrease mortality and risk of cardiovascular injury, provides cytoprotection to tissues exposed to oxidative damage, and prevents diabetes-induced perturbation. Objective: This study investigated the cardioprotective effects of L-egt on diabetes-induced cardiovascular injuries and its probable mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Many studies have used STZ to model diabetes cardiomyopathy in rats [ 15 , 16 , 17 ]. In this diabetic cardiomyopathy rat model, elevated ROS levels are presented with higher MDA levels and decreased antioxidant—such as SOD, GPx and Nrf2—expression, which then induced cardiac cell damage [ 1 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used STZ to model diabetes cardiomyopathy in rats [ 15 , 16 , 17 ]. In this diabetic cardiomyopathy rat model, elevated ROS levels are presented with higher MDA levels and decreased antioxidant—such as SOD, GPx and Nrf2—expression, which then induced cardiac cell damage [ 1 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several of the inflammatory markers we intend to measure have been shown to be modulated in protective fashion by ergothioneine in preclinical models; e.g. TNF-α [35], Nrf2 [36] and NOX4 [34]. In the context of COVID-19, a possible factor affecting measures of inflammation might be vaccination timing, and this information will be collected from participants and examined as a potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has also been revealed that NRF2 translocation was mediated by PI3K/AKT and PKC signaling pathways ( Hseu et al, 2015 , 2020 ). An in silico work indicated that Ergothioneine is an allosteric effector of NRF2, suggesting a direct interaction of Ergothioneine with NRF2 ( Dare et al, 2022 ). Alternatively, Ergothioneine influences the KEAP1–NRF2 pathway possibly via its interaction with KEAP1, a thiol-rich protein.…”
Section: Ergothioneine and Its Proposed Anti-ageing Mechanismsmentioning
confidence: 99%